An Attack On Elg-luc3-ecc Cryptosystem Using Hastad’s And Julta’s Theorem - Wong T. J; Koo L. F; Sathar M. H. A; Rasedee A. F. N.; Sarbini I. N (Lviv Polytechnic National University, 2024)
Indexed by Scopus